Análise da profundidade de desgaste e da perda mineral no esmalte subjacente à microabrasão após técnica microabrasiva. - Lima, Júlia Magalhães da Costa (2009)
The main effect of the microabrasion in the enamel is significant erosion. However, there is a gap in the literature about validated and reproducible assessment of the depth of erosion in the enamel surface which is originally curve. AIMS: Evaluate depth of erosion and mineral loss of enamel produced by microabrasion technique in original coronary surface of human teeth. METHODS AND MATERIALS: 40 extracted human molars were randomly spited in four groups, with 10 specimens each, in accordance with the microabrasive treatment: AC- 18% hydrochloric acid and pumice, AF 37% phosphoric acid and pumice, OP Opalustre and WRM Whiteness RM. Each specimens had buccal surface´s laterals isolated so that the central area received the microabrasion treatment. After this procedure, transverse slices not demineralized were prepared and submitted to microradiography and analysis in Polarized Light Microscope. One own terminology had created for the morphology of the interface enamel normal-microabrasioned. This served as base to introduction of a profilometry technique with analysis of digital images, in order to get the depth of erosion on microabrasion´s area. The Intraclass Correlation Test was applied to test technique´s reproducibility. The mineral loss and the depth which it happened had analyzed by transverses plotted at equidistant points of the limit enamel normal-microabrasioned. The dates were analyzed with ANOVA test (p < 0.05). RESULTS: The profilometry technique achieved a good reproducibility (Intraclass Correlation Test of 0,9998) and was validated internally. The AC group was the most aggressive, with a greater depth of erosion (110,51 ± 41,21 μm), and a greater mineral loss (13 ± 3 peso %), with significant difference between WRM group (p < 0,05; 9,41± 4,4 peso %) and OP group (p < 0,05; 9,0 ± 3,8 peso %). The OP group, on the other hand, was the less aggressive, with the lowest values in all parameters analyzed, presenting depth of erosion less than AC group (p < 0,0001), WRM group (p < 0,001; 86,24 ± 27,99 μm) and AF group (p < 0,05; 74,46 ± 42,06 μm). The others two groups achieved intermediate results for depth of erosion and mineral loss. The depth of mineral loss was greater than on AF group (31,38 ± 20,30 μm), however, there wasn´t statistical difference between the groups. CONCLUSIONS: Based on own terminology for the interface enamel normalmicroabrasioned and on the implementation of new technique of profilometry, the agents tested showed a significant difference in the depth of erosion, which was consistent with the mineral loss. However, there wasn´t difference in the depth of mineral loss. Furthermore the new technique of profilometry is proposed to fill a gap in the literature, allowing the determination of physical depth of erosion in areas naturally curves of hard biological tissues.